The triglyceride-glucose index as an independent associate of severe tubulointerstitial fibrosis and a predictor of renal survival in IgA nephropathy - Tang, Guijing; Wang, Anni; Zhu, Xingyu; Yu, Danyan; Chen, Hongyu; Jiang, Xue; Liu, Hong (Frontiers in Endocrinology, 2026)
BackgroundTo investigate the association of the triglyceride-glucose (TyG) index with severe tubular atrophy/interstitial fibrosis (T2 lesions) and renal outcomes in patients with IgA nephropathy (IgAN).MethodsWe retrospectively analyzed 1,791 biopsy-proven IgAN patients between October 2014 and September 2024. Receiver operating characteristic (ROC) curve analysis assessed TyG index performance for predicting T2 lesions. Multivariable logistic regression and restricted cubic spline (RCS) models were applied to assess the relationship between the TyG index and T2 lesions. Renal survival was evaluated using Kaplan-Meier analysis and Multivariable Cox regression analysis.ResultsAmong 1,791 enrolled IgAN patients, 122 (6.8%) exhibited T2 lesions. The TyG index showed predictive value for T2 lesions (AUC = 0.699, 95%CI: 0.656-0.741), with an optimal cut-off of 8.69 (specificity 64.5%, sensitivity 65.6%). After 1:1 PSM, the high-TyG group (>8.69) had a higher prevalence of severe tubulointerstitial lesions, elevated BMI, serum creatinine, 24-hour urinary protein, lower eGFR (all P < 0.001), and a higher incidence of the primary endpoint (P = 0.020). Multivariable logistic regression confirmed that a high TyG index (TyG>8.69) was independently associated with T2 lesions (OR = 2.365, 95% CI: 1.104-5.062, P = 0.027). RCS analysis indicated a linear dose-response relationship (P for overall<0.001;P for nonlinearity=0.082). Kaplan-Meier analysis showed significantly worse renal survival in the high-TyG group both before and after matching (log-rank=13.59, P<0.001 after matching). Multivariable Cox regression identified a high TyG index as an independent predictor of adverse renal outcomes (HR = 1.561, 95% CI: 1.046–2.330, P = 0.029).ConclusionThe TyG index is independently associated with severe tubulointerstitial damage and poor renal survival in IgAN, with a value >8.69 effectively identifying high-risk patients for progressive renal injury.